Komunikasi Budaya dalam Keberagaman: Tinjauan Psikologis terhadap Dinamika Interaksi Antarbudaya - Alif Yahya; Lydia Megawati; Ahmad Habib Akramullah (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
Cultural diversity demands communication skills that extend beyond verbal communication and encompass an understanding of cross-cultural values, emotions, and identities. This article examines cultural communication in a pluralistic society through a psychological approach, focusing on perception, stereotypes, empathy, and cognitive openness. Cultural perception shapes how individuals interpret social reality, but often results in stereotypes that simplify the characteristics of a group, which can hinder healthy communication. On the other hand, empathy—both affective and cognitive—plays a crucial role in building emotional understanding and perspectives toward people from different cultural backgrounds. Cognitive openness strengthens the ability to accept differences, avoid quick judgments, and increase awareness of social complexity. This combination of empathy and openness is the primary foundation for building effective and inclusive intercultural communication competencies. This article emphasizes that these competencies can be developed through education, cross-cultural experiences, and psychosocial training. In the era of globalization and digitalization, cross-cultural understanding is crucial for creating a harmonious environment in educational settings, organizations, and communities. Therefore, building empathetic, open, and stereotype-free communication is key to successful interactions in a multicultural society.